Cross-linked bond accelerated interfacial charge transfer in monolayer zinc indium sulfide (ZnIn2S4)/reduced graphene oxide (RGO) heterostructure for photocatalytic hydrogen production with mechanistic insight. Issue 15 (12th July 2019) - Du, Chun; Yan, Bo; Lin, Zhaoyong; Yang, Guowei
Abstract : By separating the photo-excited charge carriers, the cross-linked bonds enabled the monolayer ZnIn2 S4 /RGO heterostructure to produce more H2 . Abstract : Due to the shorter carrier transport distance and effective photo-induced charge separation, two-dimensional (2D) heterostructures have been extensively utilized for improving the photocatalytic performance. However, the role of the cross-linked bonds in the RGO-based heterojunction has rarely been focused on. In this study, the 2D/2D heterostructure of monolayer ZnIn2 S4 with d 10 electron configuration and graphene oxide has been synthesized. Benefiting from the existence of the cross-linked C–S bonds in the heterostructure, the interfacial carrier transfer could be accelerated in the monolayer ZnIn2 S4 /RGO heterostructure for effectively inhibiting the recombination of the photo-excited electron and hole. Under visible light irradiation, the ZnIn2 S4 /RGO heterostructure exhibited a photocatalytic performance superior to that of the ZnIn2 S4 and ZnIn2 S4 /RGO mixture, which is up to 5064 μmol g −1 h −1 . In addition, the mechanism involving the migration pathway of the interfacial electron through the cross-linked bonds was observed through the detection of the generated ˙O2 − radicals by a BMPO spin-trapping electron spin resonance technique. This work shows that the fabricated heterostructure can effectively prolong the carrier lifetime to enhance the photocatalytic efficiency through dual purpose of suppressing the recombination especially the role of the cross-linked bond, and provides an insight into the photocatalysis mechanism with evidence through experiment.